2018
DOI: 10.2174/1389450119666180326122831
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles in Cancer Treatment: Opportunities and Obstacles

Abstract: In the United States, the estimated number of new cancer cases in 2018 will be approx. 1.7 million. Historically, combination chemotherapy has been the primary choice of treatment. However, chemotherapeutics have pharmaceutical limitations, among which include problems with stability and aqueous solubility. Likewise, dose limiting toxicity is significant with nonspecific toxicity to healthy cells, hair loss, loss of appetite, peripheral neuropathy and diarrhea being typical side effects. The emergence of Multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 163 publications
(90 citation statements)
references
References 0 publications
2
84
0
Order By: Relevance
“…For example, the results of the present study indicated that IQGAP1 is a potential target for CRC treatment and further highlighted that miR-124 is in theory a potential way to antagonize IQGAP1 similar to the WW domain peptide of IQGAP1 mentioned. Recently, nanoparticles have emerged as a popular concept for targeted delivery of therapeutic agents to tumors (37)(38)(39). A type of combined polymeric nanoparticle (PNP) entrapping phosphatidyl inositol 3 kinase inhibitors or irinotecan suppresses or even eliminates lung metastasis of CRC in a BALB/C mice model, but negligible accumulation of PNPs is detected in the organs including the spleen, liver and kidneys indicating good tissue selectivity of PNPs and organ safety (40).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the results of the present study indicated that IQGAP1 is a potential target for CRC treatment and further highlighted that miR-124 is in theory a potential way to antagonize IQGAP1 similar to the WW domain peptide of IQGAP1 mentioned. Recently, nanoparticles have emerged as a popular concept for targeted delivery of therapeutic agents to tumors (37)(38)(39). A type of combined polymeric nanoparticle (PNP) entrapping phosphatidyl inositol 3 kinase inhibitors or irinotecan suppresses or even eliminates lung metastasis of CRC in a BALB/C mice model, but negligible accumulation of PNPs is detected in the organs including the spleen, liver and kidneys indicating good tissue selectivity of PNPs and organ safety (40).…”
Section: Discussionmentioning
confidence: 99%
“…78 Imaging can be successfully used for the evaluation of biodistribution and pharmacokinetics of nanomedicine-based drug delivery systems. A variety of drug delivery systems have been developed that can be classified as (1) polymeric drug carriers including polymeric micelles, 79 polymeric NPs, 80 dendrimers, 81 cyclodextrins, 82 hydrogel NPs, 83 nanocapsules, 84 microparticles, 85 microcapsules, 86 and microspheres 87 ; (2) lipid-based drug carriers including liposomes, 88 solid lipid nanocarriers, 89 phospholipid micelles, 59 niosomes, 90 and ethosomes 91 ; and (3) metal and inorganic drug carriers including gold NPs, 80 nanoshells, 92 magnetic NPs, 93 carbon nanotubes, 94 quantum dots, 95 and so on for therapy and/or diagnosis of many diseases especially cancer. 96,97 Different types of drug delivery systems used for different biomedical applications are shown in Figure 2 and the properties of smart drug delivery systems used for cancer imaging or therapy are given in Table 2. A variety of drug delivery systems have been translated into clinics including Abraxane Ò , DaunoXome Ò , Doxil Ò / Caelyx Ò , Marqibo Ò , Myocet Ò , Onivyde Ò , and so on until today.…”
Section: Drug Delivery Systemsmentioning
confidence: 99%
“…However, there are some difficulties, such as not yet well-understood physiological response to the nanoparticles, their deposition in the body and inducing inflammatory, oxidative and cytotoxic reactions. Other obstacles refer to the complicated production process, which can lead to instability of the nanoparticle over prolonged storage, as it is sensitive to changes in temperature and pressure [20].…”
Section: Nanoparticlesmentioning
confidence: 99%